ANALYSIS OF THERMODYNAMIC FUNCTIONS OF FERRUM BORIDES - Filonenko, N. Yu.; Bereza, O. Yu. (Science and Transport Progress, 2010)
The thermodynamic functions of iron boride and carbon-alloyed one Fe2(ВС) are considered. It is shown that iron boride Fe2B is quite thermodynamically stable within the temperature range from 1023 to 1223 K.